Estimation of sonodynamic treatment region with sonochemiluminescence in gel phantom. (8th June 2018) - Mashiko, Daisaku; Nishitaka, Shinya; Iwasaki, Ryosuke; Lafond, Maxime; Yoshizawa, Shin; Umemura, Shin-ichiro
Abstract: Sonodynamic treatment is a non-invasive cancer treatment using ultrasound through the generation of reactive oxygen species (ROS) by acoustic cavitation. High-intensity focused ultrasound (HIFU) can generate cavitation bubbles using highly negative pressure in its focal region. When cavitation bubbles are forced to collapse, they generate ROS, which can attack cancer cells, typically assisted by a sonodynamically active antitumor agent. For sonodynamic treatment, both localization and efficiency of generating ROS are important. To improve them, the region of ROS generation was quantitatively estimated in this study using a polyacrylamide gel containing luminol as the target exposed to "Trigger HIFU", consisting of a highly intense short "trigger pulse" to generate a cavitation cloud followed by a moderate-intensity long "sustaining burst" to keep the cavitation bubbles oscillating. It was found to be important for efficient ROS generation that the focal region of the trigger pulse should be immediately exposed to the sustaining burst.